2016
DOI: 10.1002/asia.201600941
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Construction of Pyrrolidines Bearing a Trifluoromethylated Quaternary Stereogenic Center via CuI‐Catalyzed 1,3‐Dipolar Cycloaddition of Azomethine Ylides with β‐CF3‐β,β‐Disubstituted Nitroalkenes

Abstract: A direct and convenient method has been developed for the synthesis of optically active pyrrolidines bearing a quaternary stereogenic center containing a CF3 group at the C-3 position of the pyrrolidine ring. The synthesis system, Cu(I) /Si-FOXAP-catalyzed exo-selective 1,3-dipolar cycloaddition of azomethine ylides with β-CF3 -β,β-disubstituted nitroalkenes, provides pyrrolidines with high diastereoselectivities (up to >98:2 d.r.) and excellent enantioselectivities (up to >99.9 ee) and performs well for a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Interestingly, the generation of N -metalated AYs in the presence of chiral ligands has allowed the enantioselective synthesis of pyrrolidines. , In 1991, Grigg and co-workers demonstrated, for the first time, that the addition of a stoichiometric amount of chiral cobalt or manganese complexes with ephedrine derivatives as the chiral ligand in the generation of AYs derived from imines of glycine alkyl esters could give pyrrolidines with up to 96% ee. It was also reported that silver­(I) salts in combination with chiral phosphane ligands can catalyze the 32CA reaction of AYs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the generation of N -metalated AYs in the presence of chiral ligands has allowed the enantioselective synthesis of pyrrolidines. , In 1991, Grigg and co-workers demonstrated, for the first time, that the addition of a stoichiometric amount of chiral cobalt or manganese complexes with ephedrine derivatives as the chiral ligand in the generation of AYs derived from imines of glycine alkyl esters could give pyrrolidines with up to 96% ee. It was also reported that silver­(I) salts in combination with chiral phosphane ligands can catalyze the 32CA reaction of AYs.…”
Section: Introductionmentioning
confidence: 99%
“…Different metals, such as Zn, , Ag, ,,,, and Cu, , ,,, and chiral ligands, such as 7 , 8 , ,,,,,, or 9 , ,, have been used in the 32CA reactions of N -metalated AYs with electrophilic ethylene derivatives, improving diastereo- and enantioselectivities. Interestingly, while stereoselectivities have been found to be dependent on the chiral ligands, the substitution of the electrophilic ethylene and even the nature of the metal, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Michael addition reaction, S N 2′ reaction, cycloaddition, and transition-metal catalysis are used to synthesize compounds with TFQC by using electrophilic reagents such as trifluoromethylated olefins. We have shown great interest in using α-trifluoromethylated carbanions, which are challenging starting materials, with a facile defluorination before further functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…2 These metal-catalyzed methods have successfully provided access to a wide range of substituted enantiomerically enriched pyrrolidines. 49 …”
mentioning
confidence: 99%
“…However, longer reaction times were required. The more challenging β,β-disubstituted nitroalkene 9 reacted efficiently with 1b and led to the pyrrolidine 3Lb with a good yield and enantioselectivity (entry 13). The absolute configuration of the asymmetric centers of 3Db was unequivocally assigned as 2 R , 3 S , 4 R ,and 5 S (Table 2, top right) by X-ray crystallographic analysis.…”
mentioning
confidence: 99%